2010
DOI: 10.1128/jcm.01562-10
|View full text |Cite
|
Sign up to set email alerts
|

Poor Positive Accuracy of QuickVue Rapid Antigen Tests during the Influenza A (H1N1) 2009 Pandemic

Abstract: We assessed the accuracy of positive QuickVue rapid influenza virus antigen test results. Using reverse transcription (RT)-PCR as the gold standard, 17 (37.8%) of 45 QuickVue-positive specimens were determined to be false positives. We report an unexpectedly high rate of false-positive QuickVue results during a period of high influenza A (H1N1) 2009 virus prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…RIDTs are valuable for their unique and singular capability of providing rapid point-of-care detection among all the diagnostic tools currently available for influenza. It should be noted, however, that although they have widely been shown to have high specificities and positive predictive values during peak influenza virus prevalence, three recent studies evaluating rapid antigen tests during the recent pandemic reported an unexpectedly high false-positive rate of 37.8% (116) or low specificities, of 48.1% (112) and 50.7% (88). The first study noted the limitations of being retrospective in nature and including some specimens (throat swabs) that were not approved by the kit manufacturer.…”
Section: Rapid Antigen Testsmentioning
confidence: 99%
“…RIDTs are valuable for their unique and singular capability of providing rapid point-of-care detection among all the diagnostic tools currently available for influenza. It should be noted, however, that although they have widely been shown to have high specificities and positive predictive values during peak influenza virus prevalence, three recent studies evaluating rapid antigen tests during the recent pandemic reported an unexpectedly high false-positive rate of 37.8% (116) or low specificities, of 48.1% (112) and 50.7% (88). The first study noted the limitations of being retrospective in nature and including some specimens (throat swabs) that were not approved by the kit manufacturer.…”
Section: Rapid Antigen Testsmentioning
confidence: 99%
“…Also, RADTs for influenza viruses are normally more sensitive for IV A then they are for IV B (138), although poorer performance has been noted in the detection of novel and variant strains of IV A (139)(140)(141)(142)(143)(144). Although the specificity of RADTs is considered to be good, false positives can also occur (145)(146)(147)(148)(149). Assay performance may vary depending on the age of the patient, the specimen type and adequacy, the appropriate handling and storage of the specimens, the amount of virus present in the specimens, the virus type and subtype, the emergence of new strains, and the particular assay that is selected for testing.…”
Section: Solid-phase Immunoassaysmentioning
confidence: 99%
“…Such visual detection, intended to improve the usability in near-patient diagnosis, might result in diminished test sensitivity if the dipstick signal for a positive sample is not easily distinguishable from that for negative cases by the operator. Stevenson and Loeffelholz reported weak dipstick signal intensity in nearly 43% of the positive pandemic A(H1N1)pdm09 samples tested using the QuickVue Influenza AϩB test (38). The large proportion of weak positive results could adversely affect the overall test performance due to operator-dependent error in identifying the weak signal as positive.…”
Section: Discussionmentioning
confidence: 99%